Epidemiological, Clinical, and Laboratory Features of Children With COVID-19 in Turkey - KARADAĞ, BÜLENT TANER; KEPENEKLİ KADAYİFCİ, EDA; ERDEM ERALP, ELA; YAKUT, NURHAYAT; GÖKDEMİR, YASEMİN (FRONTIERS MEDIA SA, 2021)
Objectives: The aim of this study is to identify the epidemiological, clinical, and laboratory features of coronavirus disease 2019 (COVID-19) in children. Methods: A retrospective study was conducted by pediatric infectious disease specialists from 32 different hospitals from all over Turkey by case record forms. Pediatric cases who were diagnosed as COVID-19 between March 16, 2020, and June 15, 2020 were included. Case characteristics including age, sex, dates of disease onset and diagnosis, family, and contact information were recorded. Clinical data, including the duration and severity of symptoms, were also collected. Laboratory parameters like biochemical tests and complete blood count, chest X-ray, and chest computed tomography (CT) were determined. Results: There were 1,156 confirmed pediatric COVID-19 cases. In total, male cases constituted 50.3% (n = 582) and females constituted 49.7% (n = 574). The median age of the confirmed cases was 10.75 years (4.5-14.6). Of the total cases, 90 were younger than 1 year of age (7.8%), 108 were 1-3 years of age (9.3%), 148 were 3-6 years of age (12.8%), 298 were 6-12 years of age (25.8%), 233 were 12-15 years of age (20.2%), and 268 cases were older than 15 years of age (23.2%). The most common symptom of the patients at the first visit was fever (50.4%) (n = 583) for a median of 2 days (IQR: 1-3 days). Fever was median at 38.4 degrees C (38.0-38.7 degrees C). The second most common symptom was cough (n = 543, 46.9%). The other common symptoms were sore throat (n = 143, 12.4%), myalgia (n = 141, 12.2%), dyspnea (n = 118, 10.2%), diarrhea (n = 112, 9.7%), stomachache (n = 71, 6.1%), and nasal discharge (n = 63, 5.4%). When patients were classified according to disease severity, 263 (22.7%) patients were asymptomatic, 668 (57.7%) patients had mild disease, 209 (18.1%) had moderate disease, and 16 (1.5%) cases had severe disease. One hundred and forty-nine (12.9%) cases had underlying diseases among the total cases; 56% of the patients who had severe disease had an underlying condition (p < 0.01). The need for hospitalization did not differ between patients who had an underlying condition and those who do not have (p = 0.38), but the need for intensive care was higher in patients who had an underlying condition (p < 0.01). Forty-seven (31.5%) of the cases having underlying conditions had asthma or lung disease (38 of them had asthma). Conclusions: To the best of our knowledge, this is one of the largest pediatric data about confirmed COVID-19 cases. Children from all ages appear to be susceptible to COVID-19, and there is a significant difference in symptomatology and laboratory findings by means of age distribution.
Keywords: COVID-19; pediatric; epidemiology; laboratory findings; disease severity; CORONAVIRUS DISEASE